Of Pain and Suffering: exploring the role of psychological processes in chronic pain, and development of a compassionate acceptance program for pain management (COMP.ACT) - Carvalho, Sérgio Andrade (2021)
Tese de doutoramento em Psicologia, especialidade em Psicologia Clínica, apresentada à Faculdade de Psicologia e de Ciências da Educação da Universidade de Coimbra